Developing digital proficiencies of English learners in adult education - Hauge, Leah; Durgunoğlu, Aydin Yücesan; Stewart, Janet (Frontiers in Education, 2024)
All around the globe, the development of digital skills is considered a priority because individuals are increasingly asked to interact with digital information. Digital literacy is required to communicate effectively and accomplish social and work-related tasks. Although there is a significant body of literature on the development of digital proficiencies in educational settings from elementary school to university, there is limited research with adults who are continuing their education later in life, usually outside of formal educational systems. The purpose of this paper is to report results from a study conducted with English learners in an adult education program in the U.S. The study evaluated the digital component of a new curriculum named CILIA-T (Content-Integrated Language Instruction for Adults with Technology Support), CILIA-T is a 16-module curriculum supporting adult learners to build their English skills, US History and Civics knowledge and digital proficiencies. In this study, researchers partnered with teachers to introduce part of the digital literacy content of the curriculum. There was a test given before and after the teaching. To determine the effectiveness of the digital literacy curriculum, the scores on the pre and post-tests and the duration to complete the pre and posttests were analyzed. There were also learner and teacher surveys to evaluate the usability and utility of the curriculum. Main findings indicated that explicit instruction in digital literacy skills led to significant improvement across all participants. Teachers and learners found the digital literacy curriculum to be helpful and relevant.